2018
DOI: 10.1109/tdmr.2018.2842253
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Heavy Ion Induced Defects in SiC Schottky Diodes

Abstract: Heavy ion irradiation increases the leakage current in reverse-biased SiC Schottky diodes. This work demonstrates, via molecular dynamics simulations, that a combination of bias and ion-deposited energy is required to produce the degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Point defect related features were not observed in the near infrared region extending to 900 nm wavelength, including the AB-lines attributed to the carbon antisite-vacancy pair [13] and the V-lines assigned to the Si vacancy [14]. From the molecular dynamics simulations, the maximum temperature at 20 nm from the track is reported to reach 2000 K (bias of 150 V [10]). At such temperatures, the immediate out-annealing of point defects such as vacancies and interstitials is expected, leaving only more extended lattice damage behind.…”
Section: Resultsmentioning
confidence: 95%
“…Point defect related features were not observed in the near infrared region extending to 900 nm wavelength, including the AB-lines attributed to the carbon antisite-vacancy pair [13] and the V-lines assigned to the Si vacancy [14]. From the molecular dynamics simulations, the maximum temperature at 20 nm from the track is reported to reach 2000 K (bias of 150 V [10]). At such temperatures, the immediate out-annealing of point defects such as vacancies and interstitials is expected, leaving only more extended lattice damage behind.…”
Section: Resultsmentioning
confidence: 95%
“…Ion-induced highly localized energy pulses were demonstrated and are proposed as a common mechanism for SELC degradation in SiC power MOSFETs and JBS diodes. However, no TCAD simulations were reported yet concerning the difference observed experimentally for heavy-ion irradiations at V DS irr < 350 V and V DS irr > 350 V. Moreover, in [27], molecular dynamics (MD) simulations of heavy-ion-induced defects for SiC Schottky diodes have been performed. The structure of the ion track was obtained after the first 100 ps when the energy has already dissipated into the bulk and the atoms in the core of the track have cooled down.…”
Section: Discussion On Selc Mechanismmentioning
confidence: 99%
“…The SELC via p-n junction originates from the thermal stress induced by the highly located power dissipation. The thermal transient and excessive lattice temperature probably cause the formation of permanent EDs, which remain after the switch off of the irradiated device, for example, MD simulations showed that the amorphous region along the ion track appears starting from certain values of applied V DS [27]. However, MD simulations now give rather qualitative results and there were no experimental studies yet to investigate the sites of heavy-ion impact.…”
Section: Discussion On Selc Mechanismmentioning
confidence: 99%
“…Although this increase is non-catastrophic, the device performance may become limited and compromise the long-term reliability of the device [8]. This mechanism of degradation was suggested to be the same as observed in SiC MOSFETs [9] and to be associated with the creation of extended defects in the SiC crystal (i.e., stacking faults) [10][11]. Finally, with a high enough bias, SEB is triggered, where the device gets instantly destroyed and the catastrophic failure mode is entered.…”
Section: Introductionmentioning
confidence: 95%
“…In fact, the current commercially available technologies of SiC power devices are sensitive to radiation which can increase the risk of single event effects (SEEs). Consequently, radiation tests on SiC Schottky power diodes are performed to study the susceptibility to SEE, such as single event leakage current degradation (SELC) and single event burnout (SEB) [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%